ANALISIS PELAKSANAAN TANGGUNGJAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) PADA PT. PERKEBUNAN TAMBI WONOSOBO - Setyawati Setyawati; Siti Hamidah; Eko Murdiyanto (Jurnal Dinamika Sosial Ekonomi, 2017)
The study aims to: (1) assess the understanding of CSR by PT Tambi, (2) assessimg the Implementations of CSR and, (3) assess the benefits of CSR program PT Tambi for society. The study is qualitative research, practice using case studies, making informant purposive and snow ball sampling. The collection of data technique used observation, documentation and interview. Qualitative descriptive analysis technique using data obtained, analyzed qualitatively and presented descriptively. Result of the research (1) The undersatanding of CSR by PT Tambi included in the category of compliance and only implement CSR general as set forth in the Company Law and not prioritize yet the environment surrounding the company, (2) CSR implementation by PT Tambi majority of (93%) as charity and 7% partial, (3) CSR PT Tambi benefit of 74% tangible and intangible, while 26% are intangible. Although the programs is given PT Tambi benefit society but the program still less can benefit increased economy of the community and it given the dependence of society with PT Tambi. Keyword: Corporate Social Responsibility, Comprehension, Implementation and Benefit